Pengaruh Social Media Marketing Melalui Aplikasi Tiktok Terhadap Keputusan Pembelian Online Pada Shopee Indonesia - Widiyasari, Andri Herlina; Petrus Paulus Mbette Suhendro; Zakiatuzzahrah Zakiatuzzahrah (Jurnal Bisnis Kreatif dan Inovatif, 2024)
The development of the creative digital economy in Indonesia is increasingly rapid. This change is clearly visible in people's purchasing behavior from traditional shopping to digital shopping, especially among young people, who have the potential to become the largest and dominant market share for marketers who use social media platforms. In this research the author focuses on social media as one of the Tik Tok marketing tools that is popular in the eyes of the public. The purpose of this research is to find out and test the proposed hypothesis regarding the influence of social media marketing via the Tik Tok application on consumer buying interest in the Indonesian Shopee market: a study of members of the Tik Tok @Shopee_id account. This quantitative research uses a descriptive survey method. Data collection using non-probability methods and purposive sampling methods was carried out by distributing questionnaires to 100 followers of the Tik Tok account @shopee_id. The data collected was analyzed using the SPSS 24 program and the data analysis process used the Classic Assumption Test, Simple Linear Regression Analysis, Coefficient of Determination (R2) and Partial Test (T Test) with Social Media Marketing as variable X and purchase interest as variable Y. The results of hypothesis testing in this research show that the Social Media Marketing variable (X) influences the Purchase Interest variable (Y). This is proven by the tcount value of 8.914 > ttable 1.987 and the significance value = 0.000 < 0.05. So it was concluded that the level of significant influence of social media marketing variables on purchasing interest was 44.8%, while the remaining 55.2% was influenced by other variables not examined in this research.